2021
DOI: 10.1371/journal.pone.0250541
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of SARS-CoV-2 during the first wave in Europe 2020: A systematic review

Abstract: Background A year following the onset of the COVID-19 pandemic, new infections and deaths continue to increase in Europe. Serological studies, through providing evidence of past infection, can aid understanding of the population dynamics of SARS-CoV-2 infection. Objectives This systematic review of SARS-CoV-2 seroprevalence studies in Europe was undertaken to inform public health strategies including vaccination, that aim to accelerate population immunity. Methods We searched the databases Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 90 publications
3
22
0
1
Order By: Relevance
“…Our data support several other studies demonstrating that there is no sex-related impact on the SARS-CoV-2 seroprevalence rate, as reviewed by Vaselli et al [ 25 ] and Lai et al [ 31 ]. Furthermore, our data are in line with the study from Xiang et al who showed that the decline in SARS-CoV-2 antibody levels against the viral N-protein in hospitalized patients is independent of sex and age [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data support several other studies demonstrating that there is no sex-related impact on the SARS-CoV-2 seroprevalence rate, as reviewed by Vaselli et al [ 25 ] and Lai et al [ 31 ]. Furthermore, our data are in line with the study from Xiang et al who showed that the decline in SARS-CoV-2 antibody levels against the viral N-protein in hospitalized patients is independent of sex and age [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…This method further allowed the screening for all variants of SARS-CoV-2 known so far but not their discrimination as, to date, mutations mainly affect the viral S-protein. The data obtained in this study reflect the infection-induced seroprevalence rates found for blood donors in many European countries as reviewed by Vaselli et al, [ 25 ], but also other countries with comparable health care systems such as the USA [ 26 ] and the UAE [ 27 ]. Blood donors positively screened for naturally acquired SARS-CoV-2 anti-N total antibodies were invited to participate in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…In most countries the proportion infected in the first wave up to August 2020 was less than 10% [12, 13]. Even in Iran, the first country outside China to be severely affected, seroprevalence was only 17% at the end of April 2020 [14].…”
Section: Resultsmentioning
confidence: 99%
“…In the UK the reproduction number is estimated to have fallen from about 3 at the start of the epidemic to about 0.5 in mid-April 2020, staying at around 0.8 until late summer [22, 23]. It is estimated that contact rates fell by 60% to 80% [12, 21, 24] after lockdown in comparison with the pre-pandemic period in the UK and other European countries.…”
Section: Resultsmentioning
confidence: 99%
“…A similar study performed by Hossain et al found a higher rate of seroprevalence in the USA (12.4%) compared to the seroprevalence rates in Europe (7.7%) and Asia (4.8%) [ 21 ]. The study performed by Houlihan et al in London reported that 45.3% of HCWs were seropositive [ 22 ] , and Vaselli et al reported that the seroprevalence was higher among the HCWs in the UK compared to the HCWs in the rest of Europe during the months of March and August 2020 [ 23 ]. Likewise, the study by Müller et al in the African countries found the seroprevalence to range from 0% to 45.1% [ 24 ].…”
Section: Discussionmentioning
confidence: 99%